Temperature dependence of photosynthetic reaction centre activity in Rhodospirillum rubrum - Kaftan, David; Bína, David; Koblížek, Michal (Photosynthesis research, 2019)
The influence of temperature on photosynthetic reactions was investigated by a combination of time-resolved bacteriochlorophyll fluorescence, steady-state and differential absorption spectroscopy, and polarographic respiration measurements in intact cells of purple non-sulphur bacterium Rhodospirillum rubrum. Using variable bacteriochlorophyll fluorescence, it was found that the electron-transport activity increased with the increasing temperature up to 41 °C. The fast and medium components of the fluorescence decay kinetics followed the ideal Arrhenius equation. The calculated activation energy for the fast component was Ea1 = 16 kJ mol-1, while that of the medium component was more than double, with Ea2 = 38 kJ mol-1. At temperatures between 41 and 59 °C, the electron transport was gradually, irreversibly inhibited. Interestingly, the primary charge separation remained fully competent from 20 to 59 °C as documented by both BChl fluorescence and differential absorption spectroscopy of the P870+ signal. At temperatures above 60 °C, the primary photochemistry became reversibly inhibited, which was manifested by an increase in minimal fluorescence, F0, whereas maximal fluorescence, FM, slowly declined. Finally, above 71 °C, the photosynthetic complexes began to disassemble as seen in the decline of all fluorometric parameters and the disappearance of the LH1 absorption band at 880 nm. The extended optimal temperature of photosynthetic reaction centre in a model species of Rhodospirillales adds on the evidence that the good thermostability of the photosynthetic reaction centres is present across all Alphaproteobacteria.
Keywords: fluorescence; Rhodospirillum rubrum; Temperature; Fluorescence; Photosynthesis; světlosběrné proteinové komplexy; Kinetics; teplota; kinetika; fotosyntéza; Cell Respiration; buněčné dýchání; Light-Harvesting Protein Complexes